Forced merger and efficiency in Malaysian banking - Abd Karim, M.Z. (2009)
This paper examine whether the so-called forced consolidation of the banking industry in Malaysia have increase the competitiveness of the Malaysian banks by analyzing the impact of mergers on bank efficiency. To achieve the objective, the study analyzed the performance of banks before and after the merger by estimating both cost and profit efficiency scores. The results show that only two out of the ten banks show significant improvement in the efficiency level after the merger. The results also indicate no significance difference in the efficiency level between the anchor banks and the target banks. The results suggest that the selection of anchor banks in the force merger process undertaken by the government is not necessarily based on efficiency. As such, the force merger process fails to achieve its desired objective. Hence, for the merger process to be fruitful in terms of achieving its objective to make the merged banks stronger and more efficient, the selection of anchor banks should be properly scrutinized in future merger exercises.